Estetika Kegembiraan dan Spirit Optimisme dalam Tembang Dolanan Anak Pesisir Barat Jawa Tengah - Pangestu Widya Ningrum; Sucipto Hadi Purnomo (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Children's dolanan songs are a form of traditional oral literature that grew and developed in the west coastal communities of Central Java, especially in Tegal Regency. However, along with the times, the existence of dolanan songs is increasingly rarely sung by children, both in the school and home environment, so that the positive values contained in it began to be neglected. This study aims to reveal the formula of joy and the spirit of optimism in dolanan songs for children on the west coast of Central Java through Roland Barthes' semiotic approach. The research method used is qualitative with the techniques of observation, recording, and content analysis of the lyrics of dolanan songs that are still sustainable in the community. The results show that the aesthetics of joy is reflected through simple lyrics, full of cheerfulness, and rhythms that invite children to move and interact socially. Meanwhile, the spirit of optimism can be seen in the moral messages that teach hope, enthusiasm, and togetherness in facing everyday life. Thus, dolanan songs not only function as entertainment, but also as a medium for character building and strengthening local cultural values amid the challenges of modernization.